"What Is Security?" Conference with Keynote Speaker Richard Lehman - Watkins, Howard::::::::: (1987)
Panel presentation: Dan Whitehurst, Reverend Walt Parry, Luisa Medina, Karen Humphrey, Linda Mack and Dick Keyes standing